Belle Teal - Martin, Ann M (New York Scholastic Press, 2001)
Belle Teal Harper is from a poor family in the country and beginning fifth-grade is a challenge as her grandmother's memory is slipping away and her brother and father are fighting again
5
Keywords: Family life -- Fiction; Schools -- Fiction